Developmental Outcomes of University Female Basketball Athletes As Participants in Peer Mentoring Groups - Jonathan Kroll; Kathleen McMillian-Roberts (Bowling Green State University, 2021)
Peer group mentoring can stimulate developmental outcomes for university basketball athletes. Seven female university basketball athletes from an NCAA Division III team participated in peer mentoring groups over the course of an academic year. By sharing about their lived experiences, the researchers were able to capture narratives that illuminated the impact of this developmental relationship. Thematic analysis was utilized to explore these descriptions and collate them into findings relevant for athletes, coaches, Athletics administrators, and others. Findings presented below indicate that these peer group mentoring experiences (a) nurtured synergistic relationships; (b) cultivated athletes' resilience; and (c) developed athletes' self-efficacy.